2017
DOI: 10.1051/bioconf/20170903009
|View full text |Cite
|
Sign up to set email alerts
|

Diversité des AOC – diversité des labels environnementaux- diversité des consommateurs : quelle stratégie de valorisation pour la filière viticole ?

Abstract: Résumé. L'objectif du travail est de fournir aux professionnels de la filière viticole deséléments objectifs sur la pertinence d'une stratégie collective de communication environnementale sur les vins d'AOC, de tester la pertinence d'une segmentation des consommateurs selon leur niveau d'implication vis-à-vis du vin et vis-à-vis de l'environnement, de mesurer l'interaction perçue par les consommateurs entre AOC et environnement selon le niveau de notoriété des AOCLe travail aété mené sur 4 annéesà partir d'enq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Adopting AEP in viticulture adds value to its products, which allows farmers to address consumers' expectations in a new way: they can benefit from their lower environmental impacts and produce higher-quality wine that is free of pesticide residues. Bélis-Bergouignan and Saint-Ges, (2009) and Jourjon et al, (2017) reported similar results, observing that consumer demand positively influenced adoption of agroecological innovations in viticulture. Sales revenue also had a significantly positive effect on adoption.…”
Section: Analysis Of Adoption Factors Of Agroecological Practicesmentioning
confidence: 59%
See 1 more Smart Citation
“…Adopting AEP in viticulture adds value to its products, which allows farmers to address consumers' expectations in a new way: they can benefit from their lower environmental impacts and produce higher-quality wine that is free of pesticide residues. Bélis-Bergouignan and Saint-Ges, (2009) and Jourjon et al, (2017) reported similar results, observing that consumer demand positively influenced adoption of agroecological innovations in viticulture. Sales revenue also had a significantly positive effect on adoption.…”
Section: Analysis Of Adoption Factors Of Agroecological Practicesmentioning
confidence: 59%
“…These changes lead farmers to adopt technological innovations in their practices, and more generally to position themselves in relation to society's expectations about the use of production practices with lower environmental impacts (Ghali et al, 2014;Jourjon et al, 2017;Kelley et al, 2017). Farmers must thus adopt alternative approaches that respect the environment to reduce impacts of agricultural activities on natural resources, meet consumer demand, and promote sustainable development of agriculture (Annunziata et al, 2018).…”
Section: Introductionmentioning
confidence: 99%